2020
DOI: 10.36380/jwpr.2020.2
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Egg Quality of Laying Hens Fed with Boiled Tomato Waste Powder.

Abstract: This study was performed to evaluate the effect of inclusion of boiled tomato waste powder in laying hens diet on growth performances and egg quality. Tomato waste used in this experiment was surplus and unsold mature tomato from the last harvest on the field. The tomato waste was boiled in boiling water (100 ºC) for 8 minutes to convert their lycopene structure from trans to cis, which is easily absorbed by the poultry digestive tract. In a completely randomized design, 200 Isa Brown laying hens were divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Our previous research showed that juice waste mixtures from carrot and several fruit peels (apple, mango, avocado, orange, melon and tree tomato) in the same proportion could be used up to 20% in broiler diets (Rizal et al, 2010) and after treated with rice-hull ash filtrate could be used up to 40% in broiler rations (Mahata et al, 2013). Meanwhile, tomato waste boiled for 8 minutes could be used 7% in ration of broilers (Mahata et al, 2016) and 12% in laying rations (Mahata et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research showed that juice waste mixtures from carrot and several fruit peels (apple, mango, avocado, orange, melon and tree tomato) in the same proportion could be used up to 20% in broiler diets (Rizal et al, 2010) and after treated with rice-hull ash filtrate could be used up to 40% in broiler rations (Mahata et al, 2013). Meanwhile, tomato waste boiled for 8 minutes could be used 7% in ration of broilers (Mahata et al, 2016) and 12% in laying rations (Mahata et al, 2020).…”
Section: Introductionmentioning
confidence: 99%